Persepsi Petani terhadap Pengembangan Agrowisata di Dusun Dasan Telaga, Desa Sembalun Lawang, Kecamatan Sembalun, Kabupaten Lombok Timur - APRIANTI, DEVI; DIARTA, I KETUT SURYA; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Farmers' Perceptions of Agrotourism Development in Dasan Telaga Hamlet, Sembalun Lawang Village, Sembalun District, East Lombok Regency.  The success of agrotourism development is determined by supporting geographical factors, tourism institutions, and the perception of farmers as managers who have awareness of sustainable farming management, especially in the field of agrotourism. The aim of this research is to analyze farmers' perceptions in developing agrotourism in Dasan Telaga Hamlet, Sembalun Lawang Village, Sembalun District, East Lombok Regency from the attraction, amenities, accessibility and ancillary components. The research location is Dasan Telaga Hamlet, Sembalun Lawang Village, Sembalun District, East Lombok Regency. The total sample of 48 farmers was taken using a non-probability sampling technique in the form of accidental sampling using the Slovin formula. Data collection comes from primary data and secondary data using structured interviews and documentation. Variables are measured using an ordinal scale which is analyzed using qualitative descriptive analysis. The research results show that farmers' perceptions of agrotourism development are relatively good. Judging from the attraction component, farmers are aware of and utilize the potential they already have in their area as a tourist attraction, from the amenity and accessibility components, farmers see the availability of adequate facilities and infrastructure around the agrotourism location, as well as the ancillary component with poor perceptions because of the farmers felt the lack of contribution felt by farmers from tourism institutions in the development of agrotourism. The suggestions from this research are expected to contribute ideas to farmers and the government to complement the existing deficiencies in agrotourism development, seen from the components of attraction, amenity, accessibility, and ancillary. It is also hoped that the results of this research can be used as material for consideration in developing agrotourism.